Deep Dream (The Network's Dream). - Chatonsky, Grégory (Substance: A Review of Theory & Literary Criticism, 2016)
The article offers the author's insights on a fiction involving the representation of thought and the brain, and to examine how a form of speculation can produce a technological reality that challenges certainty. Topics discussed include the Deep Dream application in which dream consists of hallucinating images, the association between the material and brain localization, and dreams are the models for understanding one's condition and the relationship between psyche and technology.